Bremsstrahlung radiation from weakly ionized laboratory plasma - Prasad R.Y.; Mishra K.D.; Singh R.N. (My University, 2025)
The binary collisions between electron-atom have been considered as a source of electromagnetic wave emission. The dispersive effect of the ambient plasma on the absorption and emission of electromagnetic waves has been studied. The Boltzmann transport equation with the collision term has been linearized and solved for the transverse dielectric constant of the ambient plasma. The absorption and emission coefficients have been evaluated for the laboratory plasma. The total electromagnetic wavo power in the frequency ωp<ω<10ωp has been calculated. The effect of the first- and second-order approximations in the collision torm on tho emission and absorption characteristics has been studied. © 1970, Taylor & Fancis Group, LLC.